A Pilot Study of Radiotherapy and Local Hyperthermia in Elderly Patients With Muscle-Invasive Bladder Cancers Unfit for Definitive Surgery or Chemoradiotherapy - Datta, Niloy Ranjan; Stutz, Emanuel; Puric, Emsad; Eberle, Brigitte; Meister, Andreas; Marder, Dietmar; Timm, Olaf; Rogers, Susanne; Wyler, Stephen; Bodis, Stephan (Frontiers in Oncology, 2019)
Purpose: To present the outcomes of a pilot study with hyperthermia (HT) and radiotherapy (RT) in elderly patients of muscle-invasive bladder cancers (MIBC) unfit for surgery or chemoradiotherapy (CTRT). Methods: 16 elderly patients with unifocal or multifocal MIBCs received a total dose of 48 Gy/16/4 weeks or 50 Gy/20 fractions/4 weeks respectively. HT with a radiofrequency HT unit was delivered once weekly for 60 minutes before RT and a mean temperature of 41.3°C was attained. Local control was assessed using RECIST criteria at 3-monthly intervals by cystoscopy with/without biopsy. Results: The median age, KPS and age-adjusted Charlson comorbidity index were 81 years, 70 and 5 respectively. At median follow-up of 18.5 months (range: 4-65), bladder preservation was 100% with satisfactory function. 11/16 patients (68.7%) had no local and/or distant failure, while isolated local, distant and combined local and distant failures were evident in 2, 2 and 1 patient respectively. Two local failures were salvaged by TUR-BT resulting in a local control rate of 93.7%. The 5-year cause-specific (CS) local disease free survival (LDFS), disease free survival (DFS) and overall survival (OS) were 64.3%, 51.6% and 67.5% respectively while 5-year non-cause-specific (NCS)-LDFS, NCS-DFS and NCS-OS were 26.5%, 23.2% and 38% respectively. None of the patients had acute or late grade 3/4 gastrointestinal or genitourinary toxicities. Conclusions: The outcomes from this pilot study indicate that thermoradiotherapy is a feasible therapeutic modality in elderly MIBC patients unfit for surgery or CTRT. HTRT is well tolerated, allows bladder preservation and function, achieves long-term satisfactory locoregional control and is devoid of significant treatment-related morbidity. This therapeutic approach deserves further evaluation in randomized studies.